Detection and molecular characterisation of feline viruses from swab samples - Abayli, Hasan; Can-Sahna, Kezban; Ozbek, Remziye; Aslan, Oznur; Tonbak, Sukru; Bulut, Hakan (Akademiai Kiado Zrt, 2021)
Feline calicivirus (FCV), feline alphaherpesvirus 1 (FHV-1) and feline panleukopenia virus (FPLV) as well as retroviral agents such as feline leukaemia virus (FeLV) and feline immunodeficiency virus (FIV) are important viral pathogens of cats. The aim of this study was to detect and characterise FHV-1, FPLV, FeLV, FIV and feline foamy virus (FFV) in oropharyngeal, nasal and conjunctival swabs from 93 cats that had been screened for FCV previously. We wanted to determine the possible risk factors for infection with these viruses. The prevalence was found to be 12.9% for FHV-1 and 9.7% for FPLV. FIV was detected only in two samples and FeLV in one sample, whereas the presence of FFV was not demonstrated in any of the clinical samples. The statistical analysis of the results showed that breed, age, health status, and lifestyle are important predisposing factors to FHV-1 (P < 0.05). For FPLV, only clinically unhealthy animals were found to be at risk (P < 0.001). Sequence analysis revealed that the two FIV-positive samples in this study contained different (A and B) subtypes of the virus. This is the first report on the occurrence of subtype A FIV in Turkey.
Keywords: feline; herpesvirus 1; panleukopenia; retroviruses